Arriaga Flórez, Mercedes e Cerrato, Daniele (2020). Laura Battiferri entre reinas, amigas y poetas. Madrid: Dykinson. - Trovato, Roberto (Revista de la Sociedad Española de Italianistas, 2023)
reseñas